Mediators of Inflammation – A Potential Source of Biomarkers in Oral Squamous Cell Carcinoma. (12th November 2018) - Tampa, Mircea; Mitran, Madalina Irina; Mitran, Cristina Iulia; Sarbu, Maria Isabela; Matei, Clara; Nicolae, Ilinca; Caruntu, Ana; Tocut, Sandra Milena; Popa, Mircea Ioan; Caruntu, Constantin; Georgescu, Simona Roxana
Abstract : Oral squamous cell carcinoma (OSCC) is the most common tumour of the oral cavity, associated with significant morbidity and mortality. It is a multifactorial condition, both genetic and environmental factors being involved in its development and progression. Its pathogenesis is not fully elucidated, but a pivotal role has been attributed to inflammation, strong evidence supporting the association between chronic inflammation and carcinogenesis. Moreover, an increasing number of studies have investigated the role of different mediators of inflammation in the early detection of OSCC. In this review, we have summarized the main markers of inflammation that could be useful in diagnosis and shed some light in OSCC pathogenesis.